2011
DOI: 10.1271/bbb.110180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutations of Lys41 and Asp102 of Bacteriorhodopsin

Abstract: Bacteriorhodopsin (BR) is a retinal protein that functions as a light-driven proton pump. In this study, six novel mutants including K41E and D102K, were obtained to verify or rule out the possibility that residues Lys41 and Asp102 are determinants of the time order of proton release and uptake, because we found that the order was reversed in another retinal protein archaerhodopsin 4 (AR4), which had different 41th and 102th residues. Our results rule out that possibility and confirm that the pK(a) of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…An earlier study has found that the sole expression of BR gene in the strain L33 without any mutation result in no significant variance in the p K a of PRC in the M state (24). However, our P77D mutant exhibits proton pumping behavior with features in between the wild‐type BR and AR4 (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An earlier study has found that the sole expression of BR gene in the strain L33 without any mutation result in no significant variance in the p K a of PRC in the M state (24). However, our P77D mutant exhibits proton pumping behavior with features in between the wild‐type BR and AR4 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Site-directed mutagenesis of BR. Gene engineering of BR-P77D was conducted according to the method by Ni et al (23,24). The BR-P77D bop gene was expressed in H. salinarium strain L33.…”
Section: Methodsmentioning
confidence: 99%
“…For photo sensors, however, the lifetime of the signaling state(s) should be long enough to efficiently transduce the light signal to the transducer protein. It has been reported that many amino acid residues in the proton‐conducting channel or near the retinal Schiff base have crucial effects on the photocycle of proton pumps . Nevertheless, the effects of amino acid residues that are not situated in the proton‐conducting channel or are far from the retinal Schiff base have received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequence identities of He AR with AR1 and BR are 94% and 57%, respectively. All key functional amino acid residues of BR are conserved in He AR, including the transmembrane Asp, Glu and Arg residues associated with proton transport .…”
Section: Introductionmentioning
confidence: 99%